(untitled) (Global Journal of Science Frontier Research, 2014)
Opacity of lens is called cataract. Blindness due to cataract increases to great extent globally, more than 50% people are experiencing profound or total loss of vision due to cataract. Oxidative damage plays major role in cataract development and defects are recorded in the antioxidant and related enzymes in lens during this disease. The mean value of GLUTATHION REDUCTASE activity is 1.463 ± 0.079 and 0.730 ± 0.062 n moles/min/mg, GLUTATHION-S-TRANSFERASE activity is 1.780 ± 0.069 and 0.545 ± 0.342 n moles/min/mg and Y-GLUTAMYL TRANSPEPTIRASE activity is 9.595 ± 0.094 and 3.7 ± 0.216 n moles/min/mg respectively for normal and cataractous lenses. An explanation for fall in GLUTATHION REDUCTASE activity would be the inhibitory effect of oxidants on the activity of reducing enzymes. The activity of GLUTATHION-S-TRANSFERASE is very low compared to GLUTATHION REDUCTASE and Y-GLUTAMYL TRANSPEPTIRASE. The turn over of GSH by Y-GLUTAMYL TRANSPEPTIRASE and GLUTATHION-S-TRANSFERASE is thought to be groups led with several factors including GSH level. Altered activity of the enzymes associated with the synthesis, catabolism and utilization of glutathione in the lens have been reported in mixed type of cataract.